Irreversible Elektroporation: aktueller Stellenwert in der fokalen Therapie des Prostatakarzinoms = Irreversible electroporation - Wendler, Johann J.; Hadaschik, Boris; Köhrmann, Kai-Uwe; Schlemmer, Heinz-Peter (Der Urologe, 2015)
Background: Irreversible electroporation (IRE), a new tissue ablation procedure available since 2007, could meet the requirements for ideal focal therapy (FT) with its postulated features, especially the absence of a thermal ablative effect. Thus far, there is no adequate tumor-entity-specific proof of its effectiveness, and its clinical application has hitherto been confined to very small patient cohorts. This also holds true for prostate cancer (PCA). Nevertheless, it is now being increasingly applied outside clinical trials - to a certain extent due to active advertising in the lay press. Aim of the study: In this study, current discrepancies between the clinical application and study situation and the approval and market implementation of the procedure are described. The media portrayal of IRE is discussed from different perspectives, particularly with reference to the FT of PCA. This is followed by a final clinical assessment of IRE using the NanoKnife® system. Discussion: Strict requirements govern new drug approvals. According to the German Drug Act (AMG), evidence of additional benefit over existing therapy must be provided through comparative clinical trials. For medicotechnical treatment procedures, on the other hand, such trial-based proof is not required according to the Medical Devices Act (MPG). The use of IRE even outside clinical trials has been actively promoted since the NanoKnife® system was put on the market. This has led to an increase in the number of uncontrolled IRE treatments of PCA in the last 2 years. The patients have to cover the high treatment costs themselves in these cases. If articles in the lay press advertise the procedure with promising but unverified contents, false hopes are raised in those concerned. This is disastrous if it delays the use of truly effective treatment options. Conclusion: IRE basically still has high potential for the treatment of malignancies; however, whether it can really be used for FT remains unclear due to the lack of data. This also holds true for the treatment of PCA. Only carefully conducted scientific research studies can clarify the unresolved issues regarding IRE of PCA. The urgently needed development of universally valid treatment standards for IRE is unnecessarily hampered by the flow commercially driven patients.